2022
DOI: 10.47604/ajep.1721
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Teachers and Learners of the Effects of COVID-19 on the Teaching and Learning process in Selected Secondary Schools in Kapiri- Mposhi District, Zambia

Abstract: Purpose: The purpose of this study was to examine the perceptions of teachers and learners of the effects of Covid-19 on the teaching and learning process in the selected secondary schools in Kapiri- Mposhi District.  Methodology: Ten schools were selected using random sampling from the urban and rural parts of the district, from which a total of 197 participants comprising 100 grade 9 and 12 learners and 97 teachers, were sampled. A questionnaire, face to face interviews and focus group discussions wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The future growth of the student engagement with a school depends on the monitoring of the educational system (Kabeta, 2020). The present study shows that head teachers are very active in adequately monitoring the overall system of the students learning.…”
Section: Discussionmentioning
confidence: 63%
“…The future growth of the student engagement with a school depends on the monitoring of the educational system (Kabeta, 2020). The present study shows that head teachers are very active in adequately monitoring the overall system of the students learning.…”
Section: Discussionmentioning
confidence: 63%
“…Hence, teacher's quality performance and engagement at work are also expected. Kabeta (2013), emphasized the effect of school leaders to the teacher's efficacy in the teaching and learning process in the classroom which leads to high student's performance. 2) indicators which is protecting instructional time and maintaining high visibility got an observed where teachers got more engaged on extracurricular activities and programs in school which may cause to lessen their focused on their instructional time and lessen their motivation in doing their work with compassion and persistence.…”
Section: School Heads' Instructional Leadership Behavior and Teachers...mentioning
confidence: 99%
“…When leaders support the teachers in any academic endeavor, surely teachers will be as energetic and enthusiastic in teaching, likewise, in any curricular work concerning students. Kabeta (2013) emphasized the effect of school leaders to the teacher's efficacy in the teaching and learning process in the classroom which leads to high student's performance.…”
Section: School Heads' Instructional Leadership Behavior and Teachers...mentioning
confidence: 99%
“…One of these studies has been on instructional leadership of head teachers. For instance, Kabeta (2015) carried a study on instructional leadership in public secondary school. This study found that the head teacher as an instructional leader plays a major role in providing quality education, the studies however did not look at the academic performance of the learners instead it focused on the teaching and learning process in general.…”
Section: Statement Of the Problemmentioning
confidence: 99%